PENGETAHUAN JENIS LAPANGAN FUTSAL YANG DIGUNAKAN DI INDONESIA PADA MAHASISWA OLAHRAGA - M.Said Zainuddin; Arifuddin Usman; Irvan Irvan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Futsal is a giant ball game modified on the field, and the rules are to be played in any place the size of a quarter of a football field; futsal is known as small football, which has the attraction to play it very enthusiastically. Many fields can be used to play futsal, such as cement which is often found in the area and plastic interlocks that have been used in every city that has a standard field. However, some fields are commonly used but not commonly used, such as standarlex, synthetic grass, vinyl and wood parquet. Knowledge of this type of field needs to be known as an introduction to the field and for adapting the type of shoe suitable for play. The presentation of material about knowledge of futsal field types is carried out by lecture, and question and answer description of futsal field types is the method in this PKM. The results of this PKM are expected to know about the futsal fields used in Indonesia.